Life expectancy of oil palm (Elaeis guineensis) infected by Ganoderma boninense in coastal soils, Malaysia: a case study. (21st July 2017) - Chen, Zi Yan; Goh, Yit Kheng; Goh, You Keng; Goh, Kah Joo
Abstract: Ganoderma boninense basal stem rot poses a serious threat to the oil palm industry. The effects of external disease symptoms and coastal soils (Briah – Typic Endoaquepts, Jawa – Typic Sulfaquepts, and Selangor – Typic Humaquepts ) on the life expectancy of the infected palms, from disease detection to death, were studied. Six-monthly censuses on disease classes for each palm were recorded between 2004 and 2012. Survival curves of disease symptoms and soil types were compared using Kaplan–Meier and log-rank methods, respectively. Ganoderma -infected palms in acid-sulphate (AS) and potential AS soils recorded lower life expectancy. Survival duration of infected palms with foliar symptoms was 12-months shorter. External factors, such as soil type may influence the survival of infected palms and soil types may pre-dispose oil palm to higher risk of Ganoderma infection. More effective Ganoderma management for palms planted on Coastal soils (with and without AS layer) have been proposed.